2017
DOI: 10.1186/s12909-017-0913-4
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills of medical students during the OSCE: Gender-specific differences in a longitudinal trend study

Abstract: BackgroundCommunication skills are essential in a patient-centred health service and therefore in medical teaching. Although significant differences in communication behaviour of male and female students are known, gender differences in the performance of students are still under-reported. The aim of this study was to analyse gender differences in communication skills of medical students in the context of an OSCE exam (OSCE = Objective Structured Clinical Examination).MethodsIn a longitudinal trend study based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 46 publications
9
35
3
5
Order By: Relevance
“…Thus, differences between 41.9 and 42.5 points (Table 2) have very little educational meaning. Similar data have also been reported by other studies (5,(9)(10)(11)(12)(13), although most of these analyzed the role of SPs as evaluators of clinical matters. Table 2.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Thus, differences between 41.9 and 42.5 points (Table 2) have very little educational meaning. Similar data have also been reported by other studies (5,(9)(10)(11)(12)(13), although most of these analyzed the role of SPs as evaluators of clinical matters. Table 2.…”
Section: Discussionsupporting
confidence: 86%
“…In conclusion, SPs and Es evaluated communication skills similarly in an OSCE setting, suggesting that health-related professionals can be used as an alternative to SPs, thus helping to lower economic costs. Our study also found a gender difference, in favor of women, in the evaluation of communications skills by both groups, thus suggesting that women demonstrate superior skills to men, which confirms recent studies (5).…”
Section: Global (%) Women (%) Men (%)supporting
confidence: 91%
See 2 more Smart Citations
“…As it is well known that communication styles of female physicians interacting with patients are consistently different from their male counterparts, we also compared the male and female students participating in the study [24].…”
Section: Gender Specific Aspects Of Communication Skillsmentioning
confidence: 99%